Urgensi Pembentukan Lembaga Alternatif Penyelesaian Sengketa Agraria dalam Upaya Optimalisasi Penyelesaian Konflik - Sigit Pratama Maulu; Fence M. Wantu; Zamroni Abdussamad (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
This study aims to analyze the urgency of establishing an alternative institution for resolving agrarian disputes in the legal system in Indonesia. Land itself functions as a social asset and a capital asset. The role of land as a social asset is interpreted as a tool to strengthen social unity in people's lives, while capital assets are interpreted as land being an essential factor for development. The interest of every person to be able to own and control land for the benefit of life is the most basic thing why there must be serious efforts in handling agrarian conflicts in Indonesia. This study identifies two main issues, namely first, what is the urgency of establishing an alternative institution for resolving agrarian disputes in an effort to optimize conflict resolution, and second, what form of alternative dispute resolution is used in an alternative institution for resolving disputes in the agrarian sector. The research method used is normative research using a statutory approach, relying on statutory regulations as the main basis for conducting analysis and producing new concepts in handling conflicts. The results of this study indicate that although in practice there are already institutions that have the authority to resolve. However, in its implementation, there are still various obstacles, both in terms of procedural and implementation in the field. This is what then encourages the presence of a new legal system ecosystem for more concrete conflict handling in the agrarian sector.